Neglected Spheno-orbital Meningioma Presenting with Unilateral Blindness (Bangladesh Journal of Neurosurgery, 2024)
Sphenoorbital meningiomas (SOM) constitutes 9% of all  intracranial meningiomas and are originated from sphenoid wing dura. They are also  called en plaque meningioma. They cause hyperostosis of involved bone and their  soft tissue growth may spread the orbit, the infratemporal fossa, and the temporal  fossa. Most patients with SOM are middle- aged women and most commonly presents  with unilateral, nonpulsating, progressive proptosis. Recently a woman with  unilateral progressive proptosis from a remote area of Bangladesh presented to us  with blindness of her left eye due to diagnostic delay. After thorough evaluation and  imaging studies, she was diagnosed with a large spheno-orbital meningioma with  extensive bony involvement of skull base and orbit.Objective: This report highlights the necessity of creating awareness among  optometrists, undergraduate medical students as well as and ophthalmologists who  are practicing in remote areas of Bangladesh about clinical presentation of  sphenoorbital meningiomas which is a benign lesion but may be a cause of unilateral  blindness if remain undiagnosed for long Bang. J Neurosurgery 2023; 13(1): 51-54